0320 Sex Differences in Sleep Quality and Biomarker Levels in Service Members and Veterans with Chronic Mild Traumatic Brain Injury. (25th May 2022) - Guedes, Vivian; Mithani, Sara; Gottshall, Jackie; Lai, Chen; Devoto, Christina; Gill, Jessica; Kenney, Kimbra; Werner, J Kent
Abstract: Introduction: Sleep disorders are highly prevalent in military populations and are frequently associated with a history of traumatic brain injury (TBI). Despite the recent increase in female representation in the military, few studies have focused on sex differences in sleep quality in military populations. In this study, we examined biological sex differences in self-reported sleep quality and blood levels of protein biomarkers of TBI in a cohort of service members and veterans with chronic mild TBI (mTBI). Methods: Participants (n=1, 121) were enrolled in the Chronic Effects of Neurotrauma Consortium (CENC)/Long Term Impact of Military Brain Injury Consortium (LIMBIC) study. Females (n=147) and males (n=974) were classified into control (n=192, no TBI history) or mTBI (n=929, positive history of mTBI) groups. Self-reported sleep quality was assessed using PSQI (Pittsburgh Sleep Quality Index). Plasma levels of glial fibrillary acidic protein (GFAP), neurofilament light chain (NfL), Tau, interleukin (IL)-10, IL-6, and tumor necrosis factor-alpha (TNFα) were analyzed using a Simoa HD-X analyzer. Results: Regression models revealed higher PSQI scores in females than males (ß(SE)=1.36(0.40), p =0.001) and in the TBI group (ß(SE)=1.97(0.36), p<0.001) in comparison to controls. TBI x sex interaction was not statistically significant. Within the mTBI group, females had higher PSQI scores (p=0.031) and GFAP levels (p<0.001) than males, which remained significant when controlling for demographics, number of mTBIs, and time since last mTBI. No other significant differences in biomarker levels were observed. In men, but not women, higher levels of GFAP were associated with lower PSQI scores (ß(SE)=-1.38(0.43), p=0.001). Conclusion: Our findings suggest sex differences in sleep quality after mTBI, providing insights into possible mechanisms underlying the development of chronic symptoms in military populations. Our results support the need for considering biological sex in the development of personalized therapeutic strategies for chronic TBI-related sleep disorders. Support (If Any): This work was supported by grant funding from: The U.S. Army Medical Research and Material Command, from the U.S. Department of Veterans Affairs Long-term Impact of Military-related Brain Injury Consortium/Chronic Effects of Neurotrauma Consortium under Award No.1I01CX002097-01 and the U.S Department of Defense under Award No.W81XWH-18-PH/TBIRP-LIMBIC.